Association Between Risk Perception and Acceptance for a Booster Dose of COVID-19 Vaccine to Children Among Child Caregivers in China - Chenyuan Qin; Ruitong Wang; Liyuan Tao; Min Liu; Jue Liu; Jue Liu; Jue Liu (Frontiers Media S.A., 2022)
BackgroundAt present, the widespread variants and the weakened immunity provided by vaccines over time have further emphasized the importance of vaccination, boosters, and prevention efforts against COVID-19. Here, this study intends to investigate the acceptability of a booster dose of COVID-19 vaccine among child caregivers, aiming to explore the association between risk perception and child vaccine acceptance.MethodsThis anonymous, national, cross-sectional survey was conducted for one week from November 12, 2021 in mainland China. The risk perception among child caregivers was assessed based on the Health Belief Model (HBM) and the individuals was equally divided into three levels according to the total preset scores of each perception dimension. Pearson χ2 test was used to compare the differences among participants stratified by sociodemographic characteristics, health status, knowledge factors and risk perception. Univariate and multivariate logistic regression models were performed to explore the associations between risk perception and the acceptance of a booster dose of COVID-19 vaccine.ResultsA total of 88.46% of 1,724 participants were willing to accept the booster dose of the COVID-19 vaccine for their children. People who lived in central China (91.93%), had a high school or polytechnic school level education (93.98%), and had a history of COVID-19 vaccination (88.80%) were more likely to accept a booster dose of the COVID-19 vaccine for their children. The complicated vaccination process (24.5%) and uncertainty about the safety (16.5%) and efficacy (21.3%) of vaccines were the three main reasons for vaccine hesitancy among child caregivers. The acceptance of the booster dose of the COVID-19 vaccine was closely related to a higher level of perceived susceptibility (moderate: aOR = 1.56, 95% CI: 1.07-2.29, P = 0.022; high: aOR = 1.75, 95% CI: 1.06-2.89, P = 0.029) and high perceived benefit (high: aOR = 7.22, 95% CI: 2.63-19.79, P < 0.001). The results were stable in the sensitivity analysis.Conclusions88.46% of child caregivers were willing to have a booster dose of COVID-19 vaccine to children, and the acceptance was closely associated with a higher level of perceived susceptibility and perceived benefit. The complicated vaccination process, uncertainty about the safety and effectiveness of COVID-19 vaccines were the main reasons for their hesitancy. Therefore, targeted public health measures to increase perceived susceptibility and benefit are still needed to meet the requirements of higher-level immunization coverage.